The application of Cyber Notary in Indonesia - Apriani, Nabilah; Alfian, Irgi; Sari, Melia Putri Purnama (Magister Hukum Universitas Semarang, 2024)
The aim of this research is to analyze cyber notary practices in civil law countries and the nature of cyber notary in terms of evidentiary value. This research needs to be conducted due to technological developments and their relation to notary practices using cyber notaries. This research is carried out using a normative legal method by studying the regulations that apply in notarial practice with the aim of seeking legal proceedings based on positive law, supported by legal regulations regarding the position of notaries and legal regulations regarding legal matters. formal and transactional electronic, and the results of the legal experts can provide an overview of the requirements that apply in notary cyber practices. The civil law system places authentic deeds as perfect evidence because they are made based on legal regulations, where notaries, as public officials, have the authority to carry out the task of making deeds. In the development of technology, many developments have occurred in the legal system, especially regarding the leeway of notaries, which has created opportunities for notary cyber concepts. The potential for notary cyber in Indonesia needs to be considered, bearing in mind that there is not yet a legal umbrella that directly regulates notary cyber in the execution of autenik deeds that have an impact on evidence. The value of proof of an authentic deed in the notary cyber concept cannot yet be put into practice because the law on the position of notary does not yet accommodate this provision, remembering that the preparation of an authentic deed must comply with the applicable provisions in order to have authentic value.